THE INDONESIAN INTER-REGIONAL SOCIAL ACCOUNTING MATRIX FOR FISCAL DECENTRALISATION ANALYSIS - Budy P. Resosudarmo; Ditya A. Nurdianto; Djoni Hartono (Faculty of Economics and Business, Universitas Gadjah Mada, 2009)
Disparities in development have long been a crucial issue in Indonesia. With regard to the new structure of the Indonesian government, it is of great interest to determine whether Indonesia should further decentralise its budget, and if so, what consequences this would have on the national economy overall. This paper develops a simple economic tool — that is an inter-regional social accounting matrix (IRSAM) multiplier — to analyse the impacts of further decentralising government fiscal policy on regional and national performances.Our simulations show the following. First, reducing gaps among regional economies and boosting the national economy through a higher fiscal transfer strategy might notachieve the same end; i.e. providing a higher transfer to regions that are lagging behind (Sulawesi and Eastern Indonesia) would most likely reduce gaps among regionaleconomies, but might impact negatively on the national economy overall. Second, in general, a more decentralised fiscal system would benefit households in Sulawesi andEastern Indonesia, whereas the same cannot be said for Java-Bali, Sumatra, and Kalimantan. Third, impacts of further fiscal transfers on labour income vary considerably depending on the region and type of labour.Keywords: regional economy, fiscal decentralisation, Social Accounting Matrix